Performance of palm oil clinker as a bio-filler with hybrid fillers in intumescent fire protective coatings for steel - S.A.S. Mustapa; N.H. Ramli Sulong (Penerbit Universiti Kebangsaan Malaysia, 2017)
Intumescent coatings are an effective method for fire protection of steel structures. The search for more environmental friendly intumescent coatings has led to the utilization of palm oil clinker (POC) as a bio-filler in solvent-borne intumescent coatings in order to improve fire protection performance, mechanical strength and water resistance of steel structures. In this research, POC and hybrid fillers are mixed with an acrylic binder and then blended with flame-retardant additives in order to produce intumescent coatings. The samples were tested using Bunsen burner test, thermogravimetry analysis, surface spread of flame test, field emission scanning electron microscopy, static immersion test, and adhesion strength test. It was found that the optimum composition of POC and hybrid fillers gives the best fire protection performance with the lowest equilibrium temperature (171.3°C), high thermal stability, good water resistance and excellent mechanical properties. The results of the surface spread of flame test show that Sample A3, A4, and A6 were classified as Class 1, which is the best classification. For Sample A6 (a hybrid formulation), the addition of aluminium hydroxide gives better water resistance with the lowest rate of weight change (<0.2%), while the addition of magnesium hydroxide enhances the bonding strength of the coating up to 125% compared with Sample A1 which only has a single filler POC. It can be concluded that the optimum composition of POC and hybrid fillers results in intumescent coating with the greatest fire protection performance.